Interim measures in arbitration proceedings - Tatjana Zoroska - Kamilovska; Tatjana Shterjova (LeXonomica, 2021)
Interim measures in arbitration proceedings are intended to provide protection of the parties’ rights in the course of the proceedings before the final award is rendered. This issue for a long time has been regarded to be rooted in public policy concerns, but gradually this power is being transferred to the arbitral tribunal itself. In the Republic of Macedonia, the issue of interim measures in international commercial arbitration is regulated in the Law on International Commercial Arbitration. The provisions of the law expressly provide for the power of the arbitral tribunal to grant interim measures, however many questions in regard of arbitral interim relief are left unsettled. The authors give an analysis of the currents state over this issue in the Republic of Macedonia, and make an attempt to provide a solid answer to the question – will the amended provisions of the UNCITRAL Model Law on International Commercial Arbitration be a good basis to overcome the perceived problems, or an approach similar to the Slovenian should be rather accepted.V arbitražnem postopku pravice strank v postopku pred izdajo končne odločbe zagotavljajo začasni ukrepi. Dolgo se je štelo, da za ta vprašanja obstajajo zadržki v javnem redu, toda počasi je bilo pooblastilo za izdajanje začasnih ukrepov preneseno na arbitražni senat. Vprašanje izdajanja začasnih ukrepov v mednarodnih trgovinskih arbitražah je v Republiki Makedoniji urejeno z Zakonom o mednarodni trgovinski arbitraži. Določbe zakona izrecno določajo pooblastila arbitražnega senata za izdajanje začasnih ukrepov, toda mnogo vprašanj ostaja neurejenih. Avtorici podajata analizo trenutnega stanja ureditve tega vprašanja v Republiki Makedoniji, skušata pa tudi podati zanesljiv odgovor na vprašanje, ali bi bile spremenjene določbe UNCITRAL Vzorčnega zakona o mednarodni trgovinski arbitraži primerno izhodišče za reševanje teh problemov, ali pa bi bilo primerneje prevzeti slovenski pristop.